A Review of Energy Efficient Technology and Carbon Trading for Reducing Carbon Emissions - , Satinder Kaur Khattra, Davinder Singh, Ritu Dogra (Archives of Current Research International, 2024)
This review addresses the energy efficient technology and carbon trading for reducing carbon emissions. Energy-efficient technologies (EET) and carbon trading are mechanisms for mitigating climate change. EET offers direct ways to reduce emissions by improving the efficiency of energy use in various sectors. The use of technologies such as Variable Frequency Drives (VFD) in compressors, enhanced thermal performance in buildings, and smart lighting systems demonstrate significant potential in cutting energy consumption and thereby emissions The roles of carbon credits in international emission trading schemes, emphasizing their dual purpose of environmental protection and revenue generation for developing nations. The study explores into various types of carbon credit projects, including the Clean Development Mechanism (CDM) and the Verified Carbon Standard (VCS), highlighting their distribution and impact across different regions. The importance of forests in carbon dioxide absorption and the challenges of ensuring permanence and accounting for carbon sequestration are also discussed. Additionally, the document examines policy recommendations, such as carbon pricing and emission reduction targets set by the Intergovernmental Panel on Climate Change (IPCC).